Development of a shared item repository for progress testing in veterinary education - Schaper, Elisabeth; van Haeften, Theo; Wandall, Jakob; Iivanainen, Antti; Penell, Johanna; Press, Charles McLean; Lekeux, Pierre; Holm, Peter (Frontiers in Veterinary Science, 2023)
Introduction Progress testing in education is an assessment principle for the measurement of students’ progress over time, e.g., from start to graduation. Progress testing offers valid longitudinal formative measurement of the growth in the cognitive skills of the individual students within the subjects of the test as well as a tool for educators to monitor potential educational gaps and mismatches within the curriculum in relation to the basic veterinary learning outcomes. Methods Six veterinary educational establishments in Denmark, Finland, Germany (Hannover), the Netherlands, Norway, and Sweden established in cooperation with the European Association of Establishments for Veterinary Education (EAEVE) a common veterinary item repository that can be used for progress testing in European Veterinary Education Establishments (VEEs), linear as well as computer adaptive, covering the EAEVE veterinary subjects and theoretical “Day One Competencies.” First, a blueprint was created, suitable item formats were identified, and a quality assurance process for reviewing and approving items was established. The items were trialed to create a database of validated and calibrated items, and the responses were subsequently psychometrically analyzed according to Modern Test Theory. Results In total, 1,836 items were submitted of which 1,342 were approved by the reviewers for trial testing. 1,119 students from all study years and all partners VEEs participated in one or more of six item trials, and 1,948 responses were collected. Responses were analyzed using Rasch Modeling (analysis of item-fit, differential item function, item-response characteristics). A total of 821 calibrated items of various difficulty levels matching the veterinary students’ abilities and covering the veterinary knowledge domains have been banked. Discussion The item bank is now ready to be used for formative progress testing in European veterinary education. This paper presents and discusses possible pitfalls, problems, and solutions when establishing an international veterinary progress test.